Verona comics - Dugan, Jennifer (Putnam/G. P. Putnam's Sons, 2020)
Told in two voices, cellist Jubilee and anxiety-ridden Ridley meet at a comic con where both of their families have booths, and begin a relationship they must hide from their parents.